Systemic complications of rheumatoid arthritis: Focus on pathogenesis and treatment - Wu, Di; Luo, Yehao; Li, Tong; Zhao, Xinyi; Lv, Ting; Fang, Gang; Ou, Peiqi; Li, Hongyi; Luo, Xiaofan; Huang, An; Pang, Yuzhou (Frontiers in Immunology, 2022)
As a systemic autoimmune disease, rheumatoid arthritis (RA) usually causes damage not only to joints, but also to other tissues and organs including the heart, kidneys, lungs, digestive system, eyes, skin, and nervous system. Excessive complications are closely related to the prognosis of RA patients and even lead to increased mortality. This article summarizes the serious complications of RA, focusing on its incidence, pathogenesis, clinical features, and treatment methods, aiming to provide a reference for clinicians to better manage the complications of RA.